Control of tidal turbine drive systems - Wang, Dingyi (2013)
In this report, the function, model and data of a tidal turbine drive system are summarized. The emphasis is placed on the methods which are used to design a controller to improve the performance of the tidal turbine drive system in the following aspect, the faster response time and less overshoot.